PENGARUH MODEL PICTURE AND PICTURE TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI SISWA DI SEKOLAH DASAR - Syawaldi, Arga; Halidjah, Siti; Margiati, K.Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analize whether there is not the effect of the picture and picture model to narrative essay writing skill for third grade studens public elementary school 14 south Pontianak. From the results of interview in narrative essay learning, from 29 students there are 13 student who difficulty to write the narrative essay. This research use experimental method, while the research design is use one group pretest-posttest design. Population and sample in this research is all of third grade students public elementary school 14 south Pontianak as many as 29 students. Data collection technique in this research are direct observation and measurement techniques. Based on data analysis result, average score of pre-test is 68,39 and average score of post-test is 76,15. Result of t test obtained ttabel at significant level =5% with db = 28 is 2,048. Because tcount Â (17,24)> ttabel (2,048), its mean Ha accepted and H0 is rejected, which means the application of picture and picture model with significant have influence to narrative writing skill for third grade students public elementary school 14 south Pontianak.Â Keywords : Influence, Picture and Picture Model, Narrative Essay, Writing skill